Development and use of integrated wetland condition index for lacustrine fringe wetlands of Lake Tana, Northwest Ethiopia - Yirga Kebede Wondim; Ayalew Wondie Melese (PLoS ONE, 2025)
This research aimed to develop an integrated wetland condition index (IWCI) for lacustrine fringe wetlands (LFWs) in Lake Tana, Northwest Ethiopia. These wetlands have been highly impacted by recessionary agriculture, water hyacinth infestation, and both short- and long-term water level fluctuations (WLFs), as well as a heavy sediment load. The lacustrine wetland condition index was developed based on four key characteristics (hydrology, water quality, sediment quality, and wetland biota) that define wetlands. Value obtained from field and laboratory measurements of each wetland hydrology, water chemistry, and sediment characteristics indicator was normalized by allocating scores based on literature information and the results of this research project from three different disturbance-level lacustrine wetlands in Lake Tana. Macrophyte, diatom, and zooplankton indicator species tests (IndVal% and p (raw)) were calculated using PAST 4.14 (PAleontological STatistics). Scores were allocated on a scale from 1 to 10, in such a way that the highest scores reflected the best conditions and the lowest scores the most disturbed and unhealthy conditions. Within each of the four sub-indexes, multiple measures were equally weighted, while the four-wetland components (hydrology, water chemistry, sediment, and biota) were weighted according to their contribution to overall wetland condition. Weights were assigned using the Decision Support System Software of DEFINITE. Finally, the total IWCI was classified into five wetland condition categories, namely: very poor or very far from the reference (0–3), poor (3–5), moderate (5–7), good (7–9), and excellent wetland condition or reference condition (9–10). The results of IWCI of the low water level period indicated that eight wetland-sampling sites were found within a moderately impacted condition (44.44%); similarly, eight wetland-sampling sites were found within a good or mildly impacted condition; and only two wetland- sampling sites (11.11%) were found in an excellent or reference condition. Thus, this IWCI developed and tested in this study could be a tool to inform decision-makers on lacustrine wetland conservation and restoration priorities throughout the Lake Tana ecosystem. For managing and restoring shore area wetlands and making policy, lacustrine fringe wetlands monitoring sites need to be established and monitored for their condition using IWCI developed and tested by this study.